PENERAPAN METODE ROLE PLAYING BERBANTUAN QUIZIZ UNTUK MENINGKATKAN MOTIVASI BELAJAR IPAS PADA SISWA KELAS III SD ISLAM ATHIRAH RACING CENTRE KOTA MAKASSAR - Rezky Tanawali; Hamzah Pagarra; A.Muh. Ali (STKIP Subang, 2026)
The Implementation of the Role Playing Method Assisted by Quizizz to Improve Learning Motivation in Science and Social Studies (IPAS) of Third Grade Students at SD Islam Athirah Racing Centre Makassar (supervised by Hamzah Pagarra, S.Kom., M.Pd. and A. Muh. Ali, S.Pd., M.Pd.). The problem addressed in this study was the low learning motivation of students in Science and Social Studies (IPAS), which has become an issue requiring attention through the implementation of more active, interactive, and enjoyable learning activities. This study aimed to improve students’ learning motivation in IPAS through the implementation of the Role Playing method assisted by Quizizz for third-grade students at SD Islam Athirah Racing Centre Makassar.This study employed a Classroom Action Research (CAR) approach conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects consisted of 15 third-grade students, comprising 7 male students and 8 female students. Data were collected through observation, learning motivation questionnaires, and documentation, while the data analysis techniques used were quantitative descriptive analysis and qualitative descriptive analysis.The results of the study showed that the implementation of the Role Playing method assisted by Quizizz had a positive impact on improving students’ learning motivation. The improvement was indicated by the increase in students’ learning motivation questionnaire results from 66.67% in Cycle I to 86.67% in Cycle II. Teacher teaching activities also improved from 46.67% in the first meeting of Cycle I to 93.33% in the second meeting of Cycle II. In addition, students’ learning activities increased from 43.33% in the first meeting of Cycle I to 90.00% in the second meeting of Cycle II, which was categorized as good. Based on the findings, it can be concluded that the implementation of the Role Playing method assisted by Quizizz was able to improve the learning motivation in Science and Social Studies (IPAS) of third-grade students at SD Islam Athirah Racing Centre Makassar.